2018
DOI: 10.21474/ijar01/8247
|View full text |Cite
|
Sign up to set email alerts
|

Production, Consumption and Nutritional Content of Five Neglected Vegetables in Two Secondary Cities of Burkina Faso.

Abstract: Korotimi traore 1,2 , charles parkouda 2 , aimée w.d.b. Guissou 1 , regine kamga 3 and aly savadogo 1 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Among these, many GLVs have similar or better nutritional qualities in comparison to indigenous leafy vegetables consumed in other parts of the world. For instance, comparable micronutrient levels are reported in indigenous GLVs (like Drumstick leaves, Pot cassia, Pumpkin leaves and Amaranth leaves) of Sub-Saharan Africa, while micronutrient levels (calcium, iron, zinc and/or beta-carotene) of some Indian Indigenous GLVs (Sweet potato leaves, Gogu leaves, Garkha leaves, Colocasia leaves and Purslane) are seen to be higher as compared to their African counterparts ( Nutritional Contributions of Important African Indigenous Vegetables, 2009 ; Uusiku et al, 2010 ; Schönfeldt and Pretorius, 2011 ; Traore et al, 2018 ; Catarino et al, 2019 ). Through our review, we also found that most indigenous GLVs contain ANFs in low amounts and have phytate and oxalate-to-mineral molar ratios lower than critical values, thus indicating low inhibitory effect of phytate and oxalate on mineral bioavailability.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, many GLVs have similar or better nutritional qualities in comparison to indigenous leafy vegetables consumed in other parts of the world. For instance, comparable micronutrient levels are reported in indigenous GLVs (like Drumstick leaves, Pot cassia, Pumpkin leaves and Amaranth leaves) of Sub-Saharan Africa, while micronutrient levels (calcium, iron, zinc and/or beta-carotene) of some Indian Indigenous GLVs (Sweet potato leaves, Gogu leaves, Garkha leaves, Colocasia leaves and Purslane) are seen to be higher as compared to their African counterparts ( Nutritional Contributions of Important African Indigenous Vegetables, 2009 ; Uusiku et al, 2010 ; Schönfeldt and Pretorius, 2011 ; Traore et al, 2018 ; Catarino et al, 2019 ). Through our review, we also found that most indigenous GLVs contain ANFs in low amounts and have phytate and oxalate-to-mineral molar ratios lower than critical values, thus indicating low inhibitory effect of phytate and oxalate on mineral bioavailability.…”
Section: Discussionmentioning
confidence: 99%
“…However, when vegetables are consumed, they comprise a different variety. A study in two urban areas of Burkina Faso showed that amaranth, okra, jute mallow, African eggplant, and black nightshade are among the most commonly consumed vegetables (Traoré et al, 2018). Consumers prefer to eat their vegetables fresh instead of dried.…”
Section: Underweight Is Still An Issue; However Overweight Is Increas...mentioning
confidence: 99%
“…Vegetables were most likely to be cooked and used in soups and sauces. However, leafy vegetables were also likely to be consumed as balls, after being boiled, wrung out, pressed, and seasoned with oil and salt (Traoré et al, 2018).…”
Section: Underweight Is Still An Issue; However Overweight Is Increas...mentioning
confidence: 99%
“…However, fruits and vegetables are crucial to a healthy diet and their intake is often below recommended levels in many low and middle income countries including Benin, Burkina Faso and Mali (e.g. Delisle et al, 2012;Frank et al, 2019;Traoré et al, 2018). In response to this challenge, the SaveVeg project aims to reduce undernutrition and micronutrient deficiencies improve income and productivity of small-scale food producers, particularly for women and youth, and expand sustainable land use in Benin, Burkina Faso, and Mali.…”
Section: Introductionmentioning
confidence: 99%